Večnamenski projekt hidroelektarn na Spodnji Savi - Širca, Andrej (Gradbeni vestnik, 2010)
On the Sava river section between Vrhovo HPP and the state border with Croatia, a chain of hydropower plants is under construction and partly in design at locations of Boštanj, Blanca, Krško, Brežice and Mokrice. A multi-purpose character of the project which provides power utilisation of the river Sava and solution to some infrastructure problems is demonstrated. Some characteristic design and construction problems are described for individual stages of the chain from the viewpoint of the civil works designer. The paper finally addresses those environmental aspects of the construction which have raised most interest among the local population.
Keywords: civil engineering; gradbeni objekti; gradbeništvo; hidroelektrarne; Spodnja Sava